2018
DOI: 10.17582/journal.aavs/2018/6.5.213.218
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Inhibition Kinetics of Crocodylus mindorensis (Philippine crocodile) Serum against Human Immunodeficiency Virus Type I Reverse Transcriptase

Abstract: The study aimed to determine the inhibition kinetics of Crocodylus mindorensis (Philippine crocodile) serum against recombinant HIV-1 Reverse Transcriptase (RT) using Enzyme-linked Immunosorbent Assay. The study utilized an experimental design where different concentrations of Philippine crocodile serum were used to determine its quantitative inhibitory effect and mechanism of inhibition against the HIV-1 reverse transcriptase activity. A colorimetric enzyme immunoassay that incorporates digoxigenin and biotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…This means that the inhibitory activity decreases as the Philippine crocodile serum concentration increases. This is similar to the previous study of Hinay and Sarol (2018), were the result could be explained by the presence of an “inhibitor of the inhibitor” in the crocodile serum. The best candidate inhibitor present in the crocodile serum with putative inhibition activity to HIV-1 is the Antimicrobial Peptides (AMPs) (Finger & Isberg, 2012).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This means that the inhibitory activity decreases as the Philippine crocodile serum concentration increases. This is similar to the previous study of Hinay and Sarol (2018), were the result could be explained by the presence of an “inhibitor of the inhibitor” in the crocodile serum. The best candidate inhibitor present in the crocodile serum with putative inhibition activity to HIV-1 is the Antimicrobial Peptides (AMPs) (Finger & Isberg, 2012).…”
Section: Resultssupporting
confidence: 92%
“…The best candidate inhibitor present in the crocodile serum with putative inhibition activity to HIV-1 is the Antimicrobial Peptides (AMPs) (Finger & Isberg, 2012). This is also supported by the study of Hinay and Sarol (2018) where Philippine crocodile serum concentration showed in vitro inhibition of HIV-1 Reverse transcriptase by high as 92.93±0.72% at 0.5 vol/vol % (Hinay and Sarol, 2018). Moreover, another putative component of the Philippine crocodile serum as described by Okada and colleagues provided a good support that the complement fragment C5a, an anaphylotoxin and a small peptidase product during complement activation, has a 30% HIV-1 Reverse transcriptase inhibitory activity (Okada, et al, 2011).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The HIV-1 RT activity after 21 days was 0.5928 ng/ well. On the other hand, a baseline Philippine crocodile serum concentration of 0.5% vol/vol was used based on the study conducted by Hinay and Sarol [9] and the cell viability results showed no cell reduction of mononuclear cells after 72 hours incubation.…”
Section: Hiv-1 Co-culture and Cell Viabilitymentioning
confidence: 99%